Peran Corporate Communication PT Paragon Technology And Innovation Dalam Mempertahankan Citra Positif Perusahaan - Sulistiawati; Intan Nabila; Alif Idzatulloh (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the role of corporate communication in building and maintaining a positive image of PT Paragon Technology and Innovation (Paragon), one of the largest cosmetic manufacturers in Indonesia. The focus of this study is to understand how internal and external communication strategies, including media relations, digital communication, and Corporate Social Responsibility (CSR) programs, are implemented effectively to strengthen the company's reputation in the eyes of stakeholders. The research method used is a literature study with a qualitative descriptive approach. Data were collected from various secondary sources, such as official company documents, scientific journals, mass media articles, and Paragon's official digital platforms. The results of the study indicate that corporate communication at Paragon plays a significant role in creating a positive company image. The implementation of internal communication based on company values, such as innovation and care, has succeeded in increasing employee loyalty. Structured media relations and digital communication strategies expand the company's positive exposure, while CSR programs that focus on education, health, women's empowerment, and the environment strengthen Paragon's relationship with the community. Regular evaluation of communication strategies ensures the effectiveness of the programs implemented.